TRPing into excitotoxic neuronal death. (January 2021) - Green, Matthew V.; West, Anne E.
Graphical abstract: Highlights: NMDA receptors bind to TRPM4 in neurons via a short intracellular domain. TRPM4 binding is required for glutamate-induced excitoxicity but not pro-survival NMDAR signaling. Small molecule inhibition of NMDAR/TRPM4 binding reduces neuronal damage in a stroke model. Abstract: It is a striking paradox that the activation of NMDA-type glutamate receptors (NMDARs) can both promote neuronal survival and induce excitotoxic cell death. Yet the molecular mechanisms that distinguish these cellular consequences have remained obscure. A recent study by Yan et al. (2020) reveals a novel interaction between NMDARs and TRPM4 that is required for NMDAR-induced neuronal death. Small molecule disruption of this interaction reduces excitotoxicity in stroke without blocking physiological NMDAR signaling.